FUTURE FOREIGN LANGUAGE TEACHERS A MODEL OF DEVELOPMENT OF TOLERANCE MINDSET BASED ON "SOFT SKILLS" (Scientific journal of the Fergana State University, 2023)
In this article, attention is paid to the fact that the activities organized in connection with the education of tolerance for future foreign language teachers include various directions of tolerance, on the one hand, the knowledge provided in the existing socio-political, philosophical sciences opinions about the priority tasks are stated.